Carbonyl reduction of 4-oxonon-2-enal (4-ONE) by Sniffer from D. magna and D.pulex. (25th February 2022) - Strehse, Jennifer S.; Hoffmann, Daniel; Protopapas, Nikolaos; Martin, Hans-Jörg; Maser, Edmund
Abstract: The α, β-unsaturated aldehydes 4-oxonon-2-enal (4ONE) and 4-hydroxynon-2-enal (4HNE) are products of unsaturated fatty acids and ROS, and can be formed in lipid-rich tissues such as neurons. As strong electrophiles, both compounds react with DNA and proteins, and are capable of inactivating enzymes. However, both the human carbonyl reductase and the carbonyl reductase Drosophila melanogaster Sniffer are known to reduce 4ONE, a major lipid peroxidation product, to a less or non-toxic form. In this study, products formed during carbonyl reduction of 4ONE and 4HNE by recombinant Sniffer proteins from Daphnia magna and Daphnia pulex were investigated. A high-performance liquid chromatography analysis showed that Sniffer from D. magna converted 35.6% of 4ONE to 11.9% HNO and 23.7% 4HNE, while D. pulex converted 34.5% of this substrate to 14.8% HNO and 19.7% 4HNE. Thus, 4HNE is the main product formed from the sniffer-mediated reduction of 4ONE. The kinetic parameters obtained from the reduction of 4ONE were K m  = 13.9 ± 2.1 μM, k cat  = 1.53 s −1, k cat /k m  = 0.11 s −1  μM −1 for D. magna Sniffer and K m  = 29.2 ± 4.3 μM, k cat  = 0.64 s −1, k cat /k m  = 0.02 s −1  μM −1 for D. pulex Sniffer . These results demonstrate that Sniffer from D. magna and D. pulex are important enzymes involved in the carbonyl reductive biotransformation of 4ONE, a cytotoxic lipid peroxidation product. Noteworthy, the catalytic properties of both Daphnia Sniffer enzymes reflect previous findings with Sniffer from Drosophila melanogaster . Highlights: Sniffer enzymes protect against cytotoxic lipid peroxidation products. Sniffer from both Daphnia species metabolise 4ONE in an efficient way. 4HNE is the main metabolite. Activities of Sniffers with 4ONE reflect those from other SDR and AKR enzymes. There are indications for carbonyl reduction of 4HNE to DHN.